Зміст - Board, Editorial; Інститут прикладних проблем механіки і математики ім. Я. С. Підстригача НАН України, Львів (Pidstryhach Institute for Applied Problems of Mechanics and Mathematics of NAS of Ukraine, 2024)
Contents in Ukrainian and English.